2020
DOI: 10.1177/0300060519897701
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the relationship between knee ultrasound and clinical symptoms in patients with thyroid dysfunction

Abstract: Objective: To determine whether musculoskeletal ultrasound (MSUS) abnormalities were associated with thyroid dysfunction. Methods: This study included 109 patients with thyroid diseases, including thyroid dysfunction or autoimmune thyroid disease. Patients were categorized as euthyroid, hypothyroid, or hyperthyroid based on their recent thyroid function tests. To evaluate MSUS, an experienced rheumatologist examined the presence of synovial fluid, synovial hypertrophy, and grade of inflammation in both gray-sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
1
6
1
Order By: Relevance
“…According to earlier research, there is no connection between the cohort of patients undergoing arthroscopic meniscal surgery and current or past smoking [ 38 ]. In contrast to our study’s findings, several researchers found that smoking increased the risk of total knee replacement surgery in women [ 39 ]. Another study came to the same conclusion as ours: Smoking does not affect the development of OA.…”
Section: Discussioncontrasting
confidence: 99%
“…According to earlier research, there is no connection between the cohort of patients undergoing arthroscopic meniscal surgery and current or past smoking [ 38 ]. In contrast to our study’s findings, several researchers found that smoking increased the risk of total knee replacement surgery in women [ 39 ]. Another study came to the same conclusion as ours: Smoking does not affect the development of OA.…”
Section: Discussioncontrasting
confidence: 99%
“…In a study, a relationship between musculoskeletal ultrasound abnormalities, knee pain and thyroid dysfunction was found. 15 Similar to our study, this study shows that thyroid function disorders worsen OA symptoms. In some studies, high TSH levels have been shown to increase the synovial fluid amount and viscosity by increasing the synthesis of hyaluronic acid and proteoglycans.…”
Section: Discussionsupporting
confidence: 89%
“…T3 could stimulate the synthesis of collagen X and the expression of matrix metalloproteinase 13 (MMP-13) and alkaline phosphatase, and promoted the progress of MMP-13, ultimately leading to cartilage mineralization and degradation [25][26][27]. Kim et al indicated that both hypothyroid and hyperthyroid states were associated with the incidence of knee arthralgia and knee osteoarthritis [10]. According to Devrimsel et al, patients with hypothyroidism had thinner femurs and a higher risk of OA than healthy individuals at all measurement sites [28].…”
Section: Discussionmentioning
confidence: 99%
“…Although the etiology and pathogenesis of OA have not yet been fully clarified, aging, obesity, infection, trauma, and metabolic disorders are considered risk factors for OA [7,8]. Recent studies have demonstrated the important role of thyroid hormone metabolism in articular cartilage maintenance and the pathogenesis of OA [9][10][11]. Thyroid hormone is essential for endochondral ossification and the expression of genes that control chondrocyte maturation and matrix synthesis [12].…”
Section: Open Accessmentioning
confidence: 99%